(3eHMK GdYdGeI GdTgGHi Ydi cdGe GdbGVi GdHjVGhi aj GdJaSjQs - (3GdTgGHis; (3GdHjVGhj , YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, fGUQ GdOjf CHh SYjO,J (B685 (3g` ? s
(3ChdgG (B:s
(3bGd JYGdi ai ShQI GdMLQ ai bUI CUMGH GdMLQ aGNPJge GdUjMI eUHMjf , bGd Gdehdi SYO ai MhGTi GdbGVi s
(3BNQgG (B:s
(3ai bUI CUMGH GdMLQ GdPjf ge bhe UGdM hGddg Gdehab s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B97s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- s
Keywords: (3GdJaSjQ hYdhe GdbQBfs